Implementasi Dakwah Islam Melalui Media Sosial Di Majlis Taklim Sabilu Taubah Di Desa Karanggayam Kecamatan Srengat Kabupaten Blitar - Soebiantoro Soebiantoro; Nik Haryanti; Engelien Yusniar Permanasari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
In the current era of globalization, the delivery of Islamic teachings cannot but use modern mass communication media, such as television, film, radio, internet, newspapers, magazines, books, and so on. The aim of this research is to determine the implementation of Islamic da'wah through social media at Majlis Taklim Sabilu Taubah in Karanggayam Village, Srengat District, Blitar Regency. Research Method: This research, based on the location of the data source, is included in the field research category, and in terms of the characteristics of the data, it is included in qualitative research, based on the discussion, it includes descriptive research using a case study approach. Data collection methods use observation, interviews and documentation. Data analysis is carried out starting from data reduction, data presentation, and drawing conclusions. Research Results: 1) Da'wah communication at Majlis Taklim Sabilu Taubah is carried out by: a) Verbally, verbal da'wah communication is held every Maghrib prayer except Friday night and Tuesday night which is delivered directly by the Kiai. b) In the book, communication of da'wah with the book is carried out after the 'Asr prayer, the book that is delivered is Al-Iklil, every Thursday night, Friday, Monday night, Tuesday, the book that is delivered is Al Hikam. c) Print media, da'wah communication with print media is held at the same time as recitation of the book, which is given to students who are unable to understand the meaning and significance of the book being studied, with themes that are in accordance with those studied in the recitation. 2) The da'wah method via social media at Majlis Taklim Sabilu Taubah is carried out by means of lectures and printed media which are distributed to students who cannot yet read and write hijaiyah letters, especially to young people who have just started learning the Koran and older students in particular. And generally, students are less able to understand the meaning and significance of the books being studied. Recitations through print media are taken from books, especially from the Qur'an and Hadith and translated into Indonesian. 3) The results of da'wah communication via social media at Majlis Taklim Sabilu Taubah can be known by: the da'wah material is quickly understood and easy to understand the meaning and meaning of the book translated through print media, the da'wah material is easily accepted by the students, the da'wah material is easily put into practice through social media , because there is immediate information and guidance.